Carrier-free enzyme immobilization by cross-linked enzyme aggregates (CLEA) technology - Yusof, Faridah; Khanahmadi, Soofia (Springer Nature, 2018)
Biocatalyst in the form of enzymes is widely used in diverse applications. Unfortunately, free enzymes are quite unstable and may undergo denaturation even under mild conditions, thus hampering their usefulness, and this may lead to higher cost in enzyme based applications. A credible solution is to immobilize the enzymes prior to usages. This procedure was proven to improve the performances in term of stability, activity and selectivity of the enzymes. In addition, separation of product from the used enzyme was made easier and enzyme recyclability was possible. However, carrier-supported enzyme immobilization suffers from many disadvantages, such as large amounts of non-catalytic mass and expensive carrier beads. Thus, to overcome this problem, cross-linked enzyme aggregates (CLEA) has been since widely researched. It involves simple procedure and has many benefits; for example, this procedure does not need purified enzyme. The technique involves an initial precipitation of enzymes using, either organic solvents, salts, non-ionic polymers or acids to obtain aggregates. It is then followed by cross-linking the aggregates by polyfunctional reagents, such as glutaryldehyde, whereby the enzyme molecules react among themselves, leading to the formation of ‘solid biocatalyst’. This chapter aims at deliberating the CLEA technique for enzyme immobilization. Lipase extracted from cocoa pod husk (CPH), an agricultural waste product, has been chosen as the model enzyme, and upon immobilization, the biocatalyst is termed as CLEA-lipase. The production of CLEA-lipase was carried out under an optimum condition and this was followed by experimental comparison with the free-form, on the temperature and pH optima and stabilities. Additionally, recyclability of CLEA-lipase was also studied. Finally, the morphology of the solid biocatalyst, which has bearings towards its activity, was examined by Field Emission Scanning Electron Microscopy (FESEM).